The acute toxicity of chemically and physically dispersed crude oil to key arctic species under arctic conditions during the open water season. (14th August 2013) - Gardiner, William W.; Word, Jack Q.; Word, Jack D.; Perkins, Robert A.; McFarlin, Kelly M.; Hester, Brian W.; Word, Lucinda S.; Ray, Collin M.
Abstract The acute toxicity of physically and chemically dispersed crude oil and the dispersant Corexit 9500 were evaluated for key Arctic species. The copepod Calanus glacialis, juvenile Arctic cod (Boreogadus saida), and larval sculpin (Myoxocephalus sp.) were tested under conditions representative of the Beaufort and Chukchi Seas during the ice‐free season. The toxicity of 3 water‐accommodated fractions (WAF) of Alaska North Slope crude oil was examined with spiked, declining exposures. A dispersant‐only test was conducted with the copepod C. glacialis. Each preparation with oil (WAF, breaking wave WAF [BWWAF], and chemically enhanced WAF [CEWAF]) produced distinct suites of hydrocarbon constituents; the total concentrations of oil were lowest in WAF and highest in CEWAF preparations. The relative sensitivity for the different species and age classes was similar within each WAF type. Median lethal concentration values based on total petroleum hydrocarbons ranged from 1.6 mg/L to 4.0 mg/L for WAF and BWWAF treatments and from 22 mg/L to 62 mg/L for CEWAF. For Corexit 9500 exposures, median lethal concentration values ranged from 17 mg/L to 50 mg/L. The differences in the relative toxicity among the accommodated fractions indicated that the majority of petroleum hydrocarbons in the CEWAF are in less acutely toxic forms than the components that dominate the WAF or BWWAF. Further evaluation showed that the parent polycyclic aromatic hydrocarbon compounds, specifically naphthalene, were highly correlated to acute toxicity. Environ Toxicol Chem 2013;32:2284–2300. © The Authors. Environmental Toxicology and Chemistry published by Wiley Peridoicals, Inc., on behalf of SETAC. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.